2003
DOI: 10.1590/s0100-879x2003000400016
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive properties of the essential oil of Ocimum gratissimum L. (Labiatae) in mice

Abstract: We have investigated the antinociceptive effects of the essential oil of Ocimum gratissimum L. (Labiatae) (EOOG) in two classical models of pain in male Swiss mice (25-35 g), the writhing test and the formalin test. At doses of 30, 100 and 300 mg/kg (po), EOOG produced a dosedependent inhibition (from 58.3 ± 4.4 to 40.7 ± 6.3, 36.4 ± 3.6 and 24.6 ± 3.6, respectively; N = 8-10, P<0.05) of acetic acid-induced writhing, causing up to a ~60% inhibition at the highest dose used, comparable to that obtained with ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
50
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 15 publications
1
50
0
2
Order By: Relevance
“…In the coastal areas of Nigeria, the plant is used in the treatment of epilepsy, high fever and diarrhea [12]. In the Savannah areas decoctions of the leaves are used to treat mental illness while O. gratissimum is used by the Ibos of Southeastern Nigeria in the management of the baby's cord, to keep the wound surfaces sterile, it is also used in the treatment of fungal infections, fever, cold and catarrh [13].…”
Section: Introductionmentioning
confidence: 99%
“…In the coastal areas of Nigeria, the plant is used in the treatment of epilepsy, high fever and diarrhea [12]. In the Savannah areas decoctions of the leaves are used to treat mental illness while O. gratissimum is used by the Ibos of Southeastern Nigeria in the management of the baby's cord, to keep the wound surfaces sterile, it is also used in the treatment of fungal infections, fever, cold and catarrh [13].…”
Section: Introductionmentioning
confidence: 99%
“…6) Recent studies demonstrated that the contents of essential oils showed anti-nociceptive effects in mice and antibacterial effects against multidrug resistant clinical isolates. 7,8) Earlier studies have reported that the fixed oil from Ocimum basilicum showed anti-ulcer properties in rat models. 9) So far there has been no in vitro study on the immunomodulatory activity of this plant.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, OG had been shown to possess diverse pharmacological properties which may be attributed to its usefulness in folk medicine. These properties include antioxidant [12,13,14] chemotherapeutic [15]; antimutagenic [16]; antidiarrhoeal [9,17,18] antinociceptive [19] insecticidal [20] hypotensive [21] and antihelmintic [22,23]. The present study investigated the acute and sub-chronic toxicity effects of the crude aqueous leaves extract of Ocimum gratissimum in rats.…”
Section: Introductionmentioning
confidence: 99%